The conceptualisation of patient-centred care: A case study of diabetes management in public facilities in southern Malawi - Martha Makwero; Adamson Muula; Felix C. Anyawu; Jude Igumbor (AOSIS, 2021)
Background: Patient-centred care (PCC) is one of the pillars of Malawi's quality of care policy initiatives. The role of PCC in facilitating quality service delivery is well documented, and its importance may heighten in chronic disease management. Yet, PCC conceptualisation is known to be context specific. Aim: The study aimed to understand the conceptualisation of PCC amongst patients, healthcare providers (HCP) and policy makers in Diabetes Mellitus (DM) management. Setting: This study was conducted in DM clinics in Southern Malawi. Methods: Our qualitative exploratory research study design used in-depth and focus group interviews. We interviewed patients with DM, HCPs and policy makers. The study used framework analysis guided by Mead and Bower's work. Results: Patient-centred care conceptualisations from groups of participants showed convergence. However, they differed in emphasis in some elements. The prominent themes emerging from the participants' conceptualisation of PCC included the following: meeting individual needs, goals and expectations, accessing medication, supporting relationship building, patient involvement, information sharing, holistic care, timeliness and being realistic. Conclusion: Patient-centred care conceptualisation in Malawi goes beyond the patient-HCP relational framework to include the technical aspects of care. Contrary to the global view, accessing medication and timeliness are major elements in PCC conceptualisation in Malawi. Whilst PCC conceptualisation is contextual, meeting expectations and needs of patients is fundamental.